2020
DOI: 10.1126/science.aay0214
|View full text |Cite|
|
Sign up to set email alerts
|

Poverty, depression, and anxiety: Causal evidence and mechanisms

Abstract: Why are people who live in poverty disproportionately affected by mental illness? We review the interdisciplinary evidence of the bidirectional causal relationship between poverty and common mental illnesses—depression and anxiety—and the underlying mechanisms. Research shows that mental illness reduces employment and therefore income, and that psychological interventions generate economic gains. Similarly, negative economic shocks cause mental illness, and antipoverty programs such as cash transfers improve m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
387
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(435 citation statements)
references
References 150 publications
38
387
2
8
Order By: Relevance
“…BMJ Global Health whereby poverty increases the risk of mental illness, while mental illness increases the risk of future poverty. 9 Since the late 1990s, cash transfer programmes emerged as a promising approach to reduce poverty, by providing financial resources to alleviate poverty in households, while at the same time stimulating behavioural change and human capital investment. [10][11][12] Cash transfers may be unconditional, which refer to money transfers without any actions required from beneficiaries; or conditional, where money is transferred to beneficiaries that meet specific behavioural requirements.…”
Section: What Do the New Findings Imply?mentioning
confidence: 99%
See 1 more Smart Citation
“…BMJ Global Health whereby poverty increases the risk of mental illness, while mental illness increases the risk of future poverty. 9 Since the late 1990s, cash transfer programmes emerged as a promising approach to reduce poverty, by providing financial resources to alleviate poverty in households, while at the same time stimulating behavioural change and human capital investment. [10][11][12] Cash transfers may be unconditional, which refer to money transfers without any actions required from beneficiaries; or conditional, where money is transferred to beneficiaries that meet specific behavioural requirements.…”
Section: What Do the New Findings Imply?mentioning
confidence: 99%
“…25 However, this review was restricted to studies that measured depressive symptoms only and had the main goal to assess broader results on health services use and health outcomes, rather than mental health specifically. In a recent review of 37 studies, McGuire and colleagues 26 reported a positive impact of cash transfers on mental health and well-being, while Ridley and colleagues 9 reported positive effects on mental health in a review of 12 cash transfer studies. However, these reviews focused mostly on adults, and no recent review has focused on children and young people in LMICs.…”
Section: What Do the New Findings Imply?mentioning
confidence: 99%
“…Broadly, mental health and psychosocial assets predict a range of positive economic, health, and empowerment outcomes (Operario, Adler, and Williams, 2004;Wuepper and Lybbert, 2017). In particular, poor mental health, self-efficacy, and hope have been posited to contribute to poverty through their effects on motivation and future-oriented decision-making Duflo, 2012;Ridley et al, 2020;Wuepper and Lybbert, 2017).…”
Section: Appendix B Additional Information On the Psychosocial Outcomesmentioning
confidence: 99%
“…The reasons for this involve multiple protective factors involving child, family and community, and many of these factors are likely to be modifiable, examples being children's coping skills, measures to alleviate poverty and food insecurity (Ridley et al, 2020), and broader community factors, including educational support and engagement from schools (Collishaw, Hammerton, et al, 2016;Collishaw, Gardner, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%